A simplified biomimetic temperature logger for recording intertidal barnacle body temperatures. (7th April 2016) - Chan, Benny K. K.; Lima, Fernando P.; Williams, Gray A.; Seabra, Rui; Wang, Hui‐Yu
Abstract: Monitoring the thermal environment and responses of indicator species is fundamental for understanding and predicting ecological consequences of ongoing and future environmental changes. With the recent development of miniaturized temperature sensors (e.g., iButtons), which can be incorporated into biomimetic loggers (e.g., robolimpets), it is possible to routinely obtain long‐term estimates of body temperatures of intertidal organisms. A crucial step in the assembly of these biomimetic devices involves removing the circuit board from an iButton, a process which is not simple and often results in damage to the electronics or loss of calibration. In this study, we describe a simplified process to assemble biomimetic loggers, and use it to build robobarnacles (mimicking tropical and subtropical barnacles of the genus Tetraclita ). The process involves copper‐coating the stainless steel case of iButtons through an electroplating process, allowing solder joints to be made to the surface casing, thus avoiding opening the iButton to make a connection with its circuit board. This approach makes the manufacturing process simpler, faster, and prevents calibration loss, but is only suitable for species large enough to accommodate a complete iButton.